Workshop Meningkatkan Kompetensi Pendidik SD Inpres Waingapu 3 Dalam Pembuatan Alat Peraga Literasi Dan Numerasi Kabupaten Sumba Timur - Elsy S.H.Taunu; Mayun E. Nggaba; Yuliana T.I.Nuhamara; Erwin Randjawali; Stevvyleni Angu Bima; Iona L. Ndakularak; Darius I. Wadu; Itha Priyastiti (BADAN PENERBIT STIEPARI PRESS, 2023)
Community service activities in the form of workshops held at SD Inpres Waingapu 3 aim to increase the competence of educators in making literacy and numeracy teaching aids. In this activity, the method used is the method of presentation, question and answer and demonstration. The result of this community service activity is an increase in the competence of educators in making literacy and numeracy teaching aids. The props demonstrated are Takalintar, Ropin (Roda Pintar), Poca ( Pohon Baca), P3 ( Papan Perkalian dan Pembgaian), Papan Variabel, Stick Alphabet, KinKa (Kincir Angka), Menjodohkan Huruf, Siput ( Simetri Putar), MAPP ( Manik-Manik Penjumlahan dan Pengurangan), dan Jarimatika. The learning media produced through this service activity are expected to add to the collection of learning media that the school already has.